Efficacy and Toxicity of Whole Pelvic Radiotherapy Versus Prostate-Only Radiotherapy in Localized Prostate Cancer: A Systematic Review and Meta-Analysis - Wang, Shilin; Tang, Wen; Luo, Huanli; Jin, Fu; Wang, Ying (Frontiers in Oncology, 2022)
BACKGROUND: There is little level 1 evidence regarding the relative efficacy and toxicity of whole pelvic radiotherapy (WPRT) compared with prostate-only radiotherapy (PORT) for localized prostate cancer. METHODS: We used Cochrane, PubMed, Embase, Medline databases and ClinicalTrials.gov to systematically search for all relevant clinical studies. The data on efficacy and toxicity were extracted for quality assessment and meta-analysis to quantify the effect of WPRT on overall survival (OS), biochemical failure-free survival (BFFS), progression-free survival (PFS), distant metastasis-free survival (DMFS), gastrointestinal (GI) toxicity and genitourinary (GU) toxicity compared with PORT. The review is registered on PROSPERO, number: CRD42021254752. RESULTS: The results revealed that compared with PORT, WPRT significantly improved 5-year BFFS and PFS, and it was irrelevant to whether the patients had undergone radical prostatectomy (RP). In addition, for the patients who did not receive RP, the 5-year DMFS of WPRT was better than that of PORT. However, WPRT significantly increased not only the grade 2 or worse (G2+) acute GI toxicity of non-RP studies and RP studies, but also the G2+ late GI toxicity of non-RP studies. Subgroup analysis of non-RP studies found that, when the pelvic radiation dose was >49Gy (equivalent-doses-in-2-Gy-fractions, EQD-2), WPRT was more beneficial to PFS than PORT, but significantly increased the risk of G2+ acute and late GU toxicity. CONCLUSIONS: Meta-analysis demonstrates that WPRT can significantly improve BFFS and PFS for localized prostate cancer than PORT, but the increased risk of G2+ acute and late GI toxicity must be considered.